"There's No Way Abraham Lincoln Could Work at Google": Fox News and the Politics of Breaking Up Big Tech. (January 2022) - Medeiros, Ben
This paper analyzes a corpus of segments from the Tucker Carlson Tonight program concerning "big tech" (focusing specifically on Google) and contextualizes this analysis within the political history of American media and technology regulation. Conservatives have long lamented the so-called liberal bias in media, but have also traditionally supported business deregulation and an antitrust approach narrowly concerned with consumer welfare. The textual analysis of Fox segments first shows that recurring complaints about the bias of Google's employees and executives is connected with its market dominance, and they frequently position corporations rather than government as the central threat to freedom. The solutions discussed, correspondingly, often favor greater structural intervention in the market to mitigate concentration's deleterious political consequences. I show how the critique on Carlson's show and recent attention to the issue from the executive branch represent a new manifestation of the theory of ideological evolution that Jack Balkin has called "ideological drift, " in which a political idea (in this case, the "Brandeisian" approach to antitrust law) changes valence in different material circumstances and thus finds new proponents.